The Effectiveness and Efficiency of the Mini Vise Manufacturing Process Practicum: A Technical and Non-Technical Perspective on the Practicum - Nugraha, Billy; K, Krisna Apriansyah; Septiani, Sri; Wahid, Taufik Nur; Maulidin, Wildan Fatchan (Tekmapro, 2025)
This study aims to evaluate the effectiveness and efficiency of both technical and non-technical aspects in the mini vise manufacturing process practicum at technical education institutions. Data was collected through questionnaires distributed to 138 respondents, consisting of students who participated in the practicum. The questionnaire measured various technical aspects such as meeting schedules, punctuality, clarity of information, consistency in delivery, and problem-solving, as well as non-technical aspects such as teaching methods, the role of practicum assistants, module content-reports, teaching and learning activities, and learning outcomes. The results indicate that, in terms of technical aspects, the majority of respondents agreed that meeting schedules (64.1%), clarity of information (68.1%), and problem-solving (77.9%) were carried out effectively, although punctuality still requires improvement, with 39.1% of respondents remaining neutral. Regarding non-technical aspects, teaching methods (81.2%), the quality of practicum assistants (81.9%), and teaching activities (81.2%) received positive assessments from most respondents. However, some areas still need further attention to improve consistency and overall respondent satisfaction. The main conclusion of this study is that the mini vise manufacturing process practicum has generally been effective and efficient, although there are several aspects that require improvement, particularly in terms of punctuality and consistency in delivery. Recommendations from this study include improving time management, enhancing the clarity of information, and providing further training for practicum assistants.